Advanced color-reflective dual-frequency cholesteric liquid crystal displays and the driving matrix. (11th February 2017) - Hsiao, Yu-Cheng; Yeh, En-Rong; Lee, Wei
ABSTRACT: We propose a novel color-reflective, dual-frequency cholesteric liquid crystal display (DFCLCD) by employing hybrid alignment treatment. The switching voltage is significantly lowered to favor the thin-film transistors used in the current display market and the response time is drastically reduced to the millisecond level while the bistability remains. Test cells with three distinct helical pitches were fabricated to demonstrate the concept of color pixels. The DFCLCD can be directly switched from the bright planar state to the light-scattering state by a low-frequency voltage pulse, and reversibly by a high-frequency pulse. A drive scheme is presented for the advanced color DFCLCD.